24-Hour observational ward management of diabetic patients presenting with hypoglycaemia: a prospective observational study. Issue 10 (22nd September 2009) - Goh, H K; Chew, D E K; Miranda, I G; Tan, L; Lim, G H
Abstract : Background: A 24 h observational ward was set up in the study hospital emergency department (ED) in September 2005 to manage a group of patients with specific conditions including hypoglycaemia that require only short focused inpatient care. Aim: To evaluate the efficacy and safety of the management of hypoglycaemia in the observational ward via criteria of successful discharge of patients from the observational ward within 24 h and the recurrence of hypoglycaemia after discharge. Methods: Hypoglycaemic patients admitted to the observational ward had their treatment and evaluation performed within 24 h. A protocol based on current available literature was formulated. Data were collected prospectively and included patient demographics, the duration and type of diabetes mellitus, current medications and treatment given. Patients were discharged only after a set of strict discharge criteria was fulfilled, and were followed up by telephone interviews at 7 and 28 days after discharge. Results: A total of 203 patients were recruited. Of these, 170 (83.7%) patients were discharged and 33 (16.3%) were transferred to an inpatient team for a longer period of treatment. The median length of stay in the observational ward was 23.0 h. Of the 170 patients discharged, 151 (88.8%) were contacted at 7 and 28 days after discharge. Six patients had symptoms of recurrent hypoglycaemia, two of whom reattended the ED and had to be admitted. The remaining four patients had mild symptoms that were self-managed at home. Two other patients reattended for conditions not related to hypoglycaemia. Nineteen patients could not be contacted, but there was no record of any reattendances at the ED among this group of patients. Conclusion: There are currently no recommendations regarding the length of stay in hospital for patients with severe hypoglycaemia. This study shows that selected patients can be treated effectively and safely in a 24 hour observational ward.